Imares new research facility at University of Costa Rica - Govaere Vicarioli, Georges (2018)
After 13 years conceptualizing important and much needed research in Costa Rica, IMARES (the Coastal, River and Estuary Engineering Research Unit at the University of Costa Rica) will start operating in a new facility during the 2018 year. The main areas of the new facility are presented.